Pengaruh Self Assessment System, Pemeriksaan Pajak, Dan Penagihan Pajak Terhadap Upaya Peningkatan Penerimaan Pajak Pertambahan Nilai (PPN) Pada Kantor Pelayanan Pajak Pratama Jakarta Sawah Besar Dua Tahun 2021 - Windy Aprilia; Licke Bieattant (Jurnal Ilmu Administrasi Publik, 2023)
This study aims to examine the effect of self-assessment system, tax audit,  and  tax  collection  efforts  against  increase  in  revenue  Value Added Tax (VAT) in Tax Office Jakarta Sawah Besar Dua. This study used  the  type  of  quantitative  research,  which  measured  by  using multiple linear regression method in SPSS program 26. The population of this study are active taxpayers registered in the Tax Office Pratama Jakarta Sawah Besar Dua 2021. Sample determined based on nonprobability sampling method, with the type of accidental sampling with a total sample of 377 respondents. The Data used in this study is the primary data in the form of a closed questionnaire. The results showed that the self-assessment system, tax audit, and tax collection significant effect on efforts to increase tax revenue. It can be concluded that the application self-assessment system resulted in nonconformity and deviations in practice so as to cause arrears taxes. In addressing these problems the tax authorities seek supervision in the form of inspection and billing which is an action so that taxpayers can immediately  pay  off  taxes  owed  and  perform  its  tax  obligations properly.